A fatal case of hemolytic disease of the fetus and newborn associated with Anti-Jka - Owaidah, Amani Y; Alsulmi, Eman (Acta Biomedica Atenei Parmensis, 2024)
Hemolytic disease of the fetus and newborn (HDFN) is predominantly associated with RhD incompatibility between maternal and fetal blood. However, other blood group systems, including Kidd, Duffy, and MNS, can also cause HDFN. While these cases typically present with mild symptomatology and favorable prognoses, severe and potentially fatal outcomes may occur. This case report delineates a fatal instance of HDFN attributed to anti-Jka antibodies. The mother (26 years old) presented with polyhydramnios upon admission and was scheduled for a cesarean section. The neonate was delivered in a hypotonic and flaccid state. Laboratory analyses revealed hemoglobin levels of 13.4 g/dL, total bilirubin of 2 mg/dL, and a strongly positive direct antihuman globulin test (DAT). Anti-Jka antibodies were eluted from the neonate’s blood. Despite aggressive therapeutic interventions, the infant succumbed within 24 hours post-partum. This case underscores the critical importance of comprehensive prenatal screening protocols for managing pregnancies complicated by alloantibodies to minor blood group systems.